THE INFLUENCE OF EXPERIENTIAL LEARNING APPROACHES AND INTERPERSONAL INTELLIGENCE ON STUDENT PPKN LEARNING OUTCOMES - Ishaq, Muhammad; Saragi, Daulat; Mursid, R. (Jurnal Ilmiah Teunuleh, 2022)
This study aims to: (1) analyze the differences in student KDP learning outcomes taught with an experiential learning approach compared to students taught with a direct instruction approach; (2) analyze the differences in KDP learning outcomes of students who have high interpersonal intelligence compared to students who have low interpersonal intelligence; and (3) analyze the interaction between experiential learning approaches and interpersonal intelligence in influencing student KDP learning outcomes in elementary schools. The sample in this study was 50 students of Class V of the State Elementary School 056587 Garbage Beach, Bahorok District. Data collection in this study through interpersonal intelligence questionnaires and ppkn learning outcomes tests. Hypothesis testing was carried out with the Two Way Anova test. The results showed that: (1) The learning outcomes of KDP students taught with an experiential learning approach were higher than those of the direct instruction approach (Fcount = 6,157 and sig. 0.017 < 0.05); (2) The learning outcomes of KDP students who have high interpersonal intelligence are higher than students who have low interpersonal intelligence (Fcount = 5.098 and sig. value 0.029 < 0.05); and (3) There is an interaction between learning approaches and interpersonal intelligence in influencing student KDP learning outcomes (Fcount = 4.285 and sig. 0.016 < 0.44).